2013
DOI: 10.3109/19401736.2013.814115
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome ofLithobates catesbeianus(Anura: Ranidae)

Abstract: The complete mitochondrial genome of Lithobates catesbeianus (Anura: Ranidae) is sequenced to analyze the gene arrangement. It is a circular molecule of 18,241 bp in length including 37 genes typically found in other frogs. The AT content of the overall base composition of L. catesbeianus is 59.9%. The length of control region is 2783 bp with 66.0% AT content. Protein-coding genes begin with ATG as start codon except except ND1 and ATP6 began with ATA, COI and ND4L with GTG, and ND2 with ATT. COI end with AGG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…The overall AT content of L. sylvaticus mt DNA is 59.3% which is similar to L. catesbeianus (59.9%) (Lin et al, 2014), while AT content of R. dybowskii, R. cf. The overall AT content of L. sylvaticus mt DNA is 59.3% which is similar to L. catesbeianus (59.9%) (Lin et al, 2014), while AT content of R. dybowskii, R. cf.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…The overall AT content of L. sylvaticus mt DNA is 59.3% which is similar to L. catesbeianus (59.9%) (Lin et al, 2014), while AT content of R. dybowskii, R. cf. The overall AT content of L. sylvaticus mt DNA is 59.3% which is similar to L. catesbeianus (59.9%) (Lin et al, 2014), while AT content of R. dybowskii, R. cf.…”
mentioning
confidence: 69%
“…The overall AT content of L. sylvaticus mt DNA is 59.3% which is similar to L. catesbeianus (59.9%) (Lin et al, 2014), while AT content of R. dybowskii, R. cf. chensinensis is located between tRNASer (AGY) and ND6 genes (Li et al, 2014a;Lin et al, 2014), while ND5 of Rana kunyuensis is located between tRNALeu (CUN) and the control region (Li et al, 2014b). ND5 of L. sylvaticus as well as L. catesbeianus, R. dybowskii and R. cf.…”
mentioning
confidence: 69%
“…This study included ten species that we sequenced ourselves and five species from GenBank; detailed information is shown in Table 1 and Fig 1. Within Table 1, The sequences with superscript numbers among the GenBank accession numbers are referenced as follows: 1, Zhou et al [17]; 2, Che et al [3]; 3; Zhou et al [18]; 4, Yan et al [11]; 5, Sumida et al [19]; 6, Lin et al [20]; 7, Ni et al [21]. This study was conducted in strict accordance with the recommendations in the Guide for the Care and Use of Laboratory Animals of the National Institutes of Health.…”
Section: Methodsmentioning
confidence: 99%
“…catesbeiana and L . sylvatica ) from GenBank [20, 21] were selected as outgroups for phylogeny and divergent time analyses. P-distances were calculated using MEGA v.7.0.…”
Section: Methodsmentioning
confidence: 99%
“…Comparative analysis showed that the longest IGN between A. americanus and Bufotes pewzowi had a high similarity (76.9%). In many vertebrates, there is usually a trnL (CUN) gene following the trnS (AGY) gene (Cheng et al, 2018;Lin et al, 2014;Ni et al, 2016;Ye et al, 2016;. However, when the trnL (CUN) gene is translocated, an IGN is left in its original position (Zhou et al, 2009).…”
Section: Control Region and Intergenic Regionsmentioning
confidence: 99%